2007
DOI: 10.1002/jmor.10546
|View full text |Cite
|
Sign up to set email alerts
|

Deer antler regeneration: Cells, concepts, and controversies

Abstract: The periodic replacement of antlers is an exceptional regenerative process in mammals, which in general are unable to regenerate complete body appendages. Antler regeneration has traditionally been viewed as an epimorphic process closely resembling limb regeneration in urodele amphibians, and the terminology of the latter process has also been applied to antler regeneration. More recent studies, however, showed that, unlike urodele limb regeneration, antler regeneration does not involve cell dedifferentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 75 publications
1
76
0
2
Order By: Relevance
“…Lincoln, 1992;Kierdorf et al, 2007;Price and Allen, 2004). However, little is known about the mechanical properties of the antler when it is used for fighting.…”
Section: Introductionmentioning
confidence: 99%
“…Lincoln, 1992;Kierdorf et al, 2007;Price and Allen, 2004). However, little is known about the mechanical properties of the antler when it is used for fighting.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous reports, the phenomenon of exfoliation of organs is closely related with regeneration [1][2][3][4][5][6]. As primate mammals, human beings have only one organ exfoliation experience all through our lives, which is the exfoliation of primary teeth.…”
mentioning
confidence: 99%
“…Electron microscopy and immunohistochemistry demonstrated early formation of a basal lamina during antler regeneration. This basal lamina is established in peripheral areas of the healing casting wound at a time when epithelialization of the more central wound areas has not yet been completed [13,15] . Histological studies further showed that the epidermal ingrowth is accompanied by that of the dermis so that, within a matter of days, the casting wound area is overlain by a layer of skin rather than just a wound epidermis [39,42] .…”
Section: Hard Antlers Antler Casting and Wound Healingmentioning
confidence: 99%
“…At present, antler regeneration is considered a stem cell-based process [13][14][15] , a view that is based on different lines of evidence. Thus, studies in red deer and fallow deer have demonstrated that the PP contains cells expressing different stem cell markers (CD9, OCT-4, Nanog, STRO-1) [15,63] .…”
Section: Histo-and Morphogenesis Of the Regenerating Antlermentioning
confidence: 99%
See 1 more Smart Citation